A review on the recent progress made on solar photovoltaic in selected countries of sub-Saharan Africa. (September 2016) - Abubakar Mas'ud, Abdullahi; Wirba, Asan Vernyuy; Muhammad-Sukki, Firdaus; Albarracín, Ricardo; Abu-Bakar, Siti Hawa; Munir, Abu Bakar; Bani, Nurul Aini
Abstract: The harmful effects of carbon emissions and carbon dioxide caused by over dependence on oil is a global issue, which is currently being addressed by encouraging renewable energy (RE) resources contribution to the energy mix. Encouraging RE is important in order to solve the unsustainable nature of electricity generation especially in the sub-Saharan African countries. One of the REs that have vast potential especially in sub-Saharan Africa is the solar energy. This paper provides an overview of the solar photovoltaic (PV) developments in selected countries of sub-Saharan Africa – in terms of research, installed capacity, solar radiation level, RE policies and the percentage of solar PV in the future energy mix of these countries. Finally, this paper identified the barriers to RE deployment and proposed scaling-up solar PV as one of the solution in the development of energy mix in these countries.